Early improvement as a resilience signal predicting later remission to antidepressant treatment in patients with Major Depressive Disorder: Systematic review and meta-analysis. (November 2017) - Wagner, Stefanie; Engel, Alice; Engelmann, Jan; Herzog, David; Dreimüller, Nadine; Müller, Marianne B.; Tadić, André; Lieb, Klaus
Abstract: Early improvement of depressive symptoms during the first two weeks of antidepressant treatment has been discussed to be a resilience signal predicting a later positive treatment outcome in patients with Major Depressive Disorder (MDD). However, the predictive value of early improvement varies between studies, and the use of different antidepressants may explain heterogeneous results. The objective of this review was to assess the predictive value of early improvement on later response and remission and to identify antidepressants with the highest chance of early improvement. We included 17 randomized controlled trials investigating early improvement in 14, 779 adult patients with MDD comparing monotherapy with an antidepressant against placebo or another antidepressant drug. 62% (range: 35–85%) of patients treated with an antidepressant and 47% (range: 21–69%) with placebo were early improver, defined as a >20%/25% symptom reduction after two weeks of treatment. Early improvement predicted response and remission after 5–12 weeks of treatment with high sensitivity (85%; 95%-CI: 84.3 to 85.7) and low to moderate specificity (54%; 95%-CI: 53.1 to 54.9). Early improver had a 8.37 fold (6.97–10.05) higher likelihood to become responder and a 6.38 fold (5.07–8.02) higher likelihood to be remitter at endpoint than non-improver. The highest early improver rates were achieved in patients treated with mirtazapine or a tricyclic antidepressant. This finding of a high predictive value of early improvement on treatment outcome may be important for treatment decisions in the early course of antidepressant treatment. Further studies should test the efficacy of such early treatment decisions. Highlights: Early improvement frequently occur independent of the applied antidepressant agent. Early non-improvement makes later remission very unlikely. In case of non-improvement the medication should be optimized. Early improvement could be easily implemented in clinical routine. The current review may inform the design of further drug trials.